Flexural Strength of Three-Unit Monolithic Zirconia FPD With Different Size of Connectors Sintered in SpeedFire Oven - bahraini, behshid. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Posthodontics.; Advisor: Ala Ali.; Committee: Aikaterini Papathanasiou, Aikaterini Kostagianni, and Mathew Finkelman.; Keywords: Dentistry, Materials Science, and Dentistry.